Komparasi Metode Weighted Product (WP) Dan Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Dalam Menentukan Pemberian Beasiswa - Angga Yogi Pratama; Selviana Yunita (STMIK Budi Darma, 2022)
Technology is currently developing quite widely, information technology is not only technology that functions to work and store data, but also information technology to send or disseminate data. in the selection of scholarships at SDN 4 Mentawa Baru Hulu Sampit in determining the PIP scholarships still using the manual method so that it can cause inefficiencies in the management of scholarship data, as well as errors in determining scholarship recipients. Data management is also done manually, this also causes the process of identifying scholarship decisions to be slow. From these problems, we need a scholarship decision support system that can use data management and also determine scholarship decisions. The author builds a scholarship acceptance decision support system by comparing the WP and SAW methods. it is hoped that this method can determine the right method to be applied in determining scholarships, and can assist school principals and school operators in processing scholarship assessments. Based on the final calculation results, the SAW method and the WP method can produce different scholarship ratings. Based on the WP = Nanang Sujana method as the best alternative and followed by other best alternatives A3, A4, A1, and A2, then the SAW method was obtained by Radhiyatul Maulida as the best alternative and followed by other alternatives A2, A3, A4, and A5. From the comparison results with the MSE (Mean Squared Error) method, the Weighted Product (WP) method produces a higher deviation value than the Simple Addative Weighting (SAW), with a comparison of the deviation value, namely the WP method = 4363,47509 while the SAW method is obtained = 4259 , 71350. Therefore, the Weighted Product (WP) method can be recommended in making scholarship selection decisions at SDN 4 Mentawa Baru Hulu Sampit.